1992
DOI: 10.1002/ijc.2910500305
|View full text |Cite
|
Sign up to set email alerts
|

Expression and splicing patterns of human papillomavirus type‐16 mrnas in pre‐cancerous lesions and carcinomas of the cervix, in human keratinocytes immortalized by HPV 16, and in cell lines established from cervical cancers

Abstract: We have analysed the splicing patterns of human papillomavirus (HPV) type-16 mRNAs in a human epithelial cell line immortalized by HPV 16 (HPKII), in cell lines established from cervical carcinomas (SiHa and CaSki) and in pre-invasive and invasive carcinomas of the cervix. The presence of mRNA species previously described, which could encode the E6, E6I, E6II, E6III, E7, E2, E2C, E4, E5 and L1 proteins, was determined, using the RNA polymerase chain reaction (PCR) technique with primers that flank unique splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
1
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 27 publications
2
55
1
3
Order By: Relevance
“…Three LSIL and two NIL/M samples were positive for both housekeeping transcripts but negative for any HPV16 transcript and were excluded in the following two paragraphs. In accordance with published data (27), the 1302^5639 spliced transcript was not detected.…”
Section: Resultssupporting
confidence: 92%
“…Three LSIL and two NIL/M samples were positive for both housekeeping transcripts but negative for any HPV16 transcript and were excluded in the following two paragraphs. In accordance with published data (27), the 1302^5639 spliced transcript was not detected.…”
Section: Resultssupporting
confidence: 92%
“…The predominant bands seen in these tissues and also in the glandular stomach and vagina/cervix, though not in the duodenum or uterus, correspond to the sizes predicted for m R N A spliced 226~409. This m R N A includes a truncated E6*I open reading frame (Smotkin et al, 1989) and the intact E7 coding sequence; this was previously found to be the predominant splicing pattern of the E6/E7 region in CIN and invasive carcinomas (Smotkin et al, 1989;Sherman et al, 1992). Equimolar amounts of the 200 and 471 nt protected bands would give a > twofold greater intensity of the upper band; we interpret the approximately equal intensities, together with the results shown in Fig.…”
Section: Structure Of Hpv-16 Mrnas Expressedmentioning
confidence: 98%
“…It is known that mRNA coding E6 and E7 is transcribed from the same promoter in the form of a bicistronic transcript, with a number of alternative splicing variants designated as E6*I-IV encoding E6*I proteins, which are truncated forms of E6. [39][40][41] Importantly, E7 is equally and efficiently translated from E6-E7 and E6*I-E7 transcripts. 42 One siRNA, Ex-18E6, was selected within the common region of E6-E7 and E6*I-E7 mRNA so that it recognized and destructed both E6-E7 and E6*I-E7 mRNA, thereby knocking down both E6 and E7 (E6E7-specific siRNA).…”
Section: Effects Of E6 Sirna On the Growth Of Hpv18-related Cancer Cellsmentioning
confidence: 99%